2020
DOI: 10.1371/journal.pntd.0008163
|View full text |Cite
|
Sign up to set email alerts
|

Different populations of Aedes aegypti and Aedes albopictus (Diptera: Culicidae) from Central Africa are susceptible to Zika virus infection

Abstract: Zika virus (ZIKV) is a Flavivirus (Flaviviridae) transmitted to humans mainly by the bite of an infected Aedes mosquitoes. Aedes aegypti is the primary epidemic vector of ZIKV and Ae. albopictus, the secondary one. However, the epidemiological role of both Aedes species in Central Africa where Ae. albopictus was recently introduced is poorly characterized. Fieldcollected strains of Ae. aegypti and Ae. albopictus from different ecological settings in Central Africa were experimentally infected with a ZIKV strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
0
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(85 citation statements)
references
References 48 publications
5
68
0
11
Order By: Relevance
“…aegypti was a modestly more efficient vector for the African ZIKV strain than Ae. albopictus which is consistent with a recent study conducted in Central Africa with the Dak84 ZIKV strain [61]. However, on Reunion Island, Ae.…”
Section: Discussionsupporting
confidence: 92%
“…aegypti was a modestly more efficient vector for the African ZIKV strain than Ae. albopictus which is consistent with a recent study conducted in Central Africa with the Dak84 ZIKV strain [61]. However, on Reunion Island, Ae.…”
Section: Discussionsupporting
confidence: 92%
“…aegypti and Ae. albopictus from Brazzaville, are able to ensure yellow fever virus [35], dengue virus [37], Zika virus [36] transmission. To clearly establish the epidemiological importance of each Aedes species in the Republic of the Congo, additional experiments including feeding behaviour patterns, covering additional locations, and spanning several seasons are needed.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti and Ae. albopictus collected in Brazzaville are able to transmit yellow fever virus [35], Zika virus [36], and dengue virus [37]. As there is no efficient vaccine (apart from yellow fever) and specific treatment against these diseases, vector control remains the cornerstone to prevent outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that local Ae. aegypti populations are able to transmit dengue [ 11 ], Zika [ 12 ] and yellow fever [ 13 ] viruses in different urban settings in Cameroon. Prevention of large outbreaks caused by these virus relies on control of Aedes vectors based on destruction of breeding sites and insecticide-based interventions such as treatment of breeding sites with larvicides, insecticide-treated nets [ 14 ] and space spraying of adulticides in emergency situations [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%